2015
DOI: 10.4049/jimmunol.1401649
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complexes Suppress IFN-γ–Induced Responses in Monocytes by Activating Discrete Members of the SRC Kinase Family

Abstract: The regulation of the innate and the adaptive immune responses are extensively intertwined and tightly regulated. Ag-driven immune responses that are modulated by immune complexes (ICs) are known to inhibit IFN-γ–dependent MHC class II expression. We have previously demonstrated that ICs dramatically inhibit IFN-γ–induced activation of human monocytes through the activation of the FcγRI signaling pathway. In the present study we further explore the mechanisms by which ICs regulate IFN-γ activation of human mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The activation of Src can result in the promotion of survival and proliferation pathways, and even induce malignant tumors (v-src) (23). Src can be activated by several factors, including high glucose and inflammatory factors TNF-α, IFN-γ and MIF (8,(24)(25)(26). In the present study, it was found that the specific Src antagonist, PP1, inhibited MIF-induced CF proliferation.…”
Section: Discussionmentioning
confidence: 50%
“…The activation of Src can result in the promotion of survival and proliferation pathways, and even induce malignant tumors (v-src) (23). Src can be activated by several factors, including high glucose and inflammatory factors TNF-α, IFN-γ and MIF (8,(24)(25)(26). In the present study, it was found that the specific Src antagonist, PP1, inhibited MIF-induced CF proliferation.…”
Section: Discussionmentioning
confidence: 50%
“…Surprisingly, the phosphatase SHP‐1 was also required for immune complex‐mediated suppression of the immune response, as demonstrated by studies with cells from mice deficient in this protein. Additional studies uncovered other cellular components of this regulatory pathway; Src and Lyn were identified as discreet members of the Src kinase family that are necessary for the functional activity of immune complexes to regulate the immune response, as well as Syk kinase ( Fig. B ).…”
Section: Fcγri‐dependent Inhibition Of Ifnγ Signalingmentioning
confidence: 99%
“…The regulation of the innate and the adaptive immune responses are extensively intertwined and tightly regulated. Ag-driven immune responses that are modulated by immune complexes (ICs) are known to inhibit IFN-g-dependent MHC class II expression (Boekhoudt et al, 2015). Past research has led to the general conclusion that IFN-g is much more than an interferon, in that it has broader effects on the various arms of the immune system than most any other lymphokines or cytokines.…”
Section: Introductionmentioning
confidence: 99%